2011
DOI: 10.1177/1753193411433226
|View full text |Cite
|
Sign up to set email alerts
|

De la Caffinière thumb trapeziometacarpal joint arthroplasty: 16–26 year follow-up

Abstract: Seventy-one patients (93 implants) had a de la Caffinière prosthesis implanted between 1980 and 1989 and were reviewed and reported in 1997. We reviewed this series 10 years later. Similar outcome measures were used as in the original study, pinch and grip strength measured and validated outcome scores obtained (DASH and EQ-5D). Radiographic outcome was assessed. Twenty-six patients with 39 implants were available for review at a mean of 19 years (range, 16-26 years). Survivorship at 26 years was 73.9% (95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
34
0
8

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 20 publications
2
34
0
8
Order By: Relevance
“…This study demonstrates that the ARPE thumb CMC joint prosthesis is a reliable option for patients with thumb CMC arthritis of Stage III and for some patients of Stage IV of the Eaton classification in patients with medium-high level of functional demand. As suggested by others (Johnston et al, 2012), it should also be emphasized that there is a need to create a joint registry to record implant failure and revision rates.…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrates that the ARPE thumb CMC joint prosthesis is a reliable option for patients with thumb CMC arthritis of Stage III and for some patients of Stage IV of the Eaton classification in patients with medium-high level of functional demand. As suggested by others (Johnston et al, 2012), it should also be emphasized that there is a need to create a joint registry to record implant failure and revision rates.…”
Section: Discussionmentioning
confidence: 99%
“…Van Capelle et al (1999) and Chakrabarti et al (1997) reported a survival of greater than 16 years (72% and 89%, respectively) for the de la Caffinière prosthesis. Johnston et al (2012) Table 2. Results of measurements of radiological displacement of the implant (see Figure 4).…”
Section: Discussionmentioning
confidence: 99%
“…43 However, satisfactory power, thumb mobility, and pain relief were present in 74% of patients at long-term follow-up. 43,44 In 1997, Calandruccio and Jobe 45 introduced a spherical implant made of yttrium-stabilized zirconia, called the Orthosphere. Based on nearly universal adverse radiographic findings at medium-term follow-up, the inventors discontinued use of the implant.…”
Section: Trapeziectomymentioning
confidence: 99%